The polymorphic and contradictory aspects of intermittent hypoxia - Almendros, Isaac (American Physiological Society, 2014)
Intermittent hypoxia (IH) has been extensively studied during the last decade, primarily as a surrogate model of sleep apnea. However, IH is a much more pervasive phenomenon in human disease, is viewed as a potential therapeutic approach, and has also been used in other disciplines, such as in competitive sports. In this context, adverse outcomes involving cardiovascular, cognitive, metabolic, and cancer problems have emerged in obstructive sleep apnea-based studies, whereas beneficial effects of IH have also been identified. Those a priori contradictory findings may not be as contradictory as initially thought. Indeed, the opposite outcomes triggered by IH can be explained by the specific characteristics of the large diversity of IH patterns applied in each study. The balance between benefits and injury appears to primarily depend on the ability of the organism to respond and activate adaptive mechanisms to IH. In this context, the adaptive or maladaptive responses can be generally predicted by the frequency, severity, and duration of IH. However, the presence of underlying conditions such as hypertension or obesity, as well as age, sex, or genotypic variance, may be important factors tilting the balance between an appropriate homeostatic response and decompensation. Here, the two possible facets of IH as derived from human and experimental animal settings will be reviewed.